Influence of immunological markers of cardiovascular risk on atherosclerosis early development in patients with rheumatoid arthritis - Fushtey, Ivan; Podsevahina, Svitlana; Palamarchuk, Olexandr; Tkachenko, Olga (ScienceRise: Medical Science, 2019)
Aim of the study. To investigate the peculiarities of immunological markers of systemic inflammation in patients with rheumatoid arthritis (RA) depending on the clinical-immunological variant of the course of RA and on the duration of the disease. Materials and methods. We examined 82 patients with RA, aged (37.6±5,1) years. The history of the disease was less than 3 years in 47.5 % of patients (n=39) and in 52.5 % of patients (n=43) – it was more than 3 years. In 48 (58.5 %) patients a seropositive variant of RA was observed and 34 (41.5 %) patients were with seronegative variant of the disease. All patients underwent a complex clinical, laboratory and immunological examination. RA activity was assessed using the DAS 28 index; immune-enzyme assay method was used to assess the level of rheumatoid factor (RF), antibodies to cyclic citrulinated peptide (ACCP), C-reactive protein (CRP), proinflammatory cytokines (tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and IL-6). Results. The levels of pro-inflammatory cytokines in RA showed a statistically significant increase in their concentration in all groups of examined patients compared with the control one. The highest levels of TNF-α (p=0.046) and IL-1β (p=0.025) were in the group of patients with the seronegative variant of RA lasting less than 3 years; the highest concentration of IL-6 (p=0.018) was determined in patients with a long course of seropositive RA. Correlation analysis allowed determining the association of hyperproduction of TNF-α, IL-1β and IL-6 with the duration of RA and disease activity. In all groups of patients with RA an increase in the serum CRP concentration was detected. It was more expressed in patients with a seropositive variant of RA with a disease duration of more than 3 years. In addition, correlation links between CRP and IL-6, IL-1β, TNF-α have been established. The direct correlation between the level of CRP and the DAS28 index (p<0.0001), RF concentration, ACCP (p=0.05) was also revealed. Conclusions. A study in the serum of mediators of immune inflammation in patients with different clinical and immunological variants and duration of RA revealed differences in their content. In patients with anamnesis of RA less than 3 years, a predominant increase in TNF-α and IL-1β was detected in case of a seronegative disease type. In patients with a disease duration of seropositive RA for more than 3 years, the content of IL-6 was increased largely, compared with rates in patients with a similar duration of the seronegative disease. In patients with a RA seropositive duration of more than 3 years, the CRP content was 1.3 times (p=0.05) higher than in the group of patients with a history of the disease less than 3 years and 1,6 times (p=0.001) higher than in patients with similar duration of seronegative RA